Решите уравнения: 1) (х-3)^3-(х-5)^2(х+1)+4=0 2) 87+(2х-5)^3+х(х-3)^2-х(3х+1)^2=0 3) 4-х(х-6)^2=(4-х)^3
Решите уравнения: 1) (х-3)^3-(х-5)^2(х+1)+4=0 2) 87+(2х-5)^3+х(х-3)^2-х(3х+1)^2=0 3) 4-х(х-6)^2=(4-х)^3
Ответ(ы) на вопрос:
1) (х-3)^3-(х-5)^2(х+1)+4=0 (х-3)^3= (x^3-3x^2-6x^2+18x+9x-27) (х-5)^2(х+1)=(x^3+x^2-10x^2-10x+25x+25) (x^3-3x^2-6x^2+18x+9x-27)-(x^3+x^2-10x^2-10x+25x+25)+4=0 x^3-3x^2-6x^2+18x+9x-27-x^3-x^2+10x^2+10x-25x-25+4=0 если все сократить получиться 12x-48=0 x=4
Не нашли ответ?
Похожие вопросы